2006
DOI: 10.1063/1.2405898
|View full text |Cite
|
Sign up to set email alerts
|

A Gas Embedded Z-pinch Driven by SPEED2 Generator

Abstract: A gas embedded Z-pinch has been implemented using the SPEED2 generator (4.1 PF equivalent Marx generator capacity, 300 kV, 4 MA in short circuit, 187 kJ, 400 ns rise time, dI/dta10 13 A/s). Initial conditions to produce a gas embedded z-pinch with enhanced stability by means resistive effects and by finite Larmor radius effects were obtained and electrodes were constructed in order to obtain a double column Z-pinch and a hollow discharge. Experiments were carried out in deuterium at mega amperes currents . Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In the last few years, some work [13][14][15][16][17][18] has been done on the development of small PF devices operating in the range of tens to hundreds of joules of capacitor bank energy instead of Kilojoule or Megajoule. Recently [19,20], an ultra miniature PF device of less than 1 J capacitor bank energy has been constructed to observe the plasma dynamics at very low energies. The PF with smaller bank energies can actually be operated at a much higher repetition rate which will be one of the main requirements for the application of this device as future production level extreme ultra-violet (EUV) microlithography source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, some work [13][14][15][16][17][18] has been done on the development of small PF devices operating in the range of tens to hundreds of joules of capacitor bank energy instead of Kilojoule or Megajoule. Recently [19,20], an ultra miniature PF device of less than 1 J capacitor bank energy has been constructed to observe the plasma dynamics at very low energies. The PF with smaller bank energies can actually be operated at a much higher repetition rate which will be one of the main requirements for the application of this device as future production level extreme ultra-violet (EUV) microlithography source.…”
Section: Introductionmentioning
confidence: 99%
“…The size of their device was in the order of 25 cm ×25 cm × 50 cm. More recently, Soto et al [19] have observed the evidence of pinching in electrical signals in their ultra miniature device (nanfocus: NF) of 0.1 J. The total size of the NF device is 20 cm ×20 cm × 5 cm.…”
Section: Introductionmentioning
confidence: 99%